ANALISIS DAYA TERIMA DAN KANDUNGAN ZAT GIZI COOKIES BERBAHAN DASAR TEPUNG KACANG MERAH (PHASEOLUS VULGARIS L) DAN TEPUNG IKAN TERI NASI (STELEPHORUS SPP) SEBAGAI MAKANAN TAMBAHAN - Reni Ekawahyuni; Suaebah; Didik Hariyadi (Jurusan Gizi Poltekkes Pontianak, 2026)
Background: Additional food has a nutritional content according to needs and is balanced against the expected target. Anchovies (Stolephorus sp.) and red beans, with their high calcium content, contribute to the increased calcium content in processed food products. Cookies are a type of snack or dry cake consumed by various groups of people, most of whom are toddlers, schoolchildren, and adults. Objective: To determine the acceptability and nutritional content of cookies made from red bean flour and anchovy flour as additional food. Method: This study employs an experimental Completely Randomized Design (CRD) method, specifically an organoleptic test with three treatments (F1, F2, and F3), to assess the impact of panelist acceptance on color, aroma, taste, and texture. The analysis was conducted on 25 semi-trained panelists who underwent the Friedman test. Determining the nutritional content was carried out to determine the protein, carbohydrate, fat, water content, ash content, fiber content, and calcium content of the cookies. Results: The study found that the F1 formula was the most preferred cookie in terms of color, aroma, taste, and texture. Cookies in the best treatment had a nutritional content of 13.10% protein, 42.07% carbohydrates, 2.93% calcium, 27.06% fat content, 7.04% water content, 2.95% ash content, and 7.79% fiber content.